Chasing Harry Winston - Weisberger, Lauren, 1977- (New York : Pocket Books, 2010)
A trio of best friends in Manhattan agree to change their lives in the most personal and dramatic way possible -- and within one calendar year.
Keywords: Young women -- New York (State) -- New York -- Fiction; Female friendship -- Fiction; Chick lit; Manhattan (New York, N.Y.) -- Fiction; New York (State) -- Fiction; Humorous fiction